2002
DOI: 10.1073/pnas.052710299
|View full text |Cite
|
Sign up to set email alerts
|

Genetic instability favoring transversions associated with ErbB2-induced mammary tumorigenesis

Abstract: It has been argued that genetic instability is required to generate the myriad mutations that fuel tumor initiation and progression and, in fact, patients with heritable cancer susceptibility syndromes harbor defects in specific genes that normally maintain DNA integrity. However, the vast majority of human cancers arise sporadically, in the absence of deficiencies in known ''mutator'' genes. We used a cII-based mutation detection assay to show that the mean frequency of forward mutations in primary mammary ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…FVB NeuN mice crossed with C57BL/6 mice exhibit attenuated mammary tumor formation and increased tumor latency (32) and female mice develop tumors only after they experienced two to four pregnancies (33). The influence of strain background on mammary gland lesion incidence and phenotypes in WAP-TGF␣ Tgs has recently been described by Rose-Hellekant et al (34).…”
Section: Discussionmentioning
confidence: 99%
“…FVB NeuN mice crossed with C57BL/6 mice exhibit attenuated mammary tumor formation and increased tumor latency (32) and female mice develop tumors only after they experienced two to four pregnancies (33). The influence of strain background on mammary gland lesion incidence and phenotypes in WAP-TGF␣ Tgs has recently been described by Rose-Hellekant et al (34).…”
Section: Discussionmentioning
confidence: 99%
“…The first study of this kind found no increase in the number of mutant lacI transgenes rescued from thymic tumors (43). However, two of three subsequent transgene rescue studies detected increased mutation (34,44,45). For example, a recent study reported that 5-fold more mutant lacZ transgenes were rescued from pristaneinduced mouse plasmacytomas than from normal splenocytes (45).…”
Section: Discussionmentioning
confidence: 99%
“…It was reasonable to anticipate that cells in the polyoma virus middle T antigen tumor model might exhibit reduced genetic stability, because Ras pathway activation has been linked to genetic instability (31)(32)(33). In addition, mouse mammary cancers induced by chronic c-erbB2 overexpression, which also disrupts cell cycle regulation, have been shown to be genetically unstable (34).…”
mentioning
confidence: 99%
“…In the 10-30% of human breast cancers with abnormal ErbB-2, it is found that overexpression by increase of transcription or amplification of the gene is involved, rather than activation by mutations. The mouse strain used by Liu et al in this study (4), therefore, uses the mouse mammary tumor virus long terminal repeat sequences to drive expression of the erbB-2 gene. This results in overexpression of the gene specifically in the mammary glands and has been shown to result in mammary tumors in mice (10,11).…”
mentioning
confidence: 99%
“…The importance of the article by Liu et al (4) is the finding that a gene that is not thought to be involved in repair of DNA damage or maintenance of its integrity affects the occurrence of mutations. In particular, the type of mutations recovered in the mammary tumor tissues when ErbB-2 is overexpressed bears no resemblance to those found when mismatch repair is altered.…”
mentioning
confidence: 99%